Failure and Maintenance of Flexible Pavement: A Case Study of Mahendranagar City Roads, Nepal - Khadka, Rabin; Negi, Crimsan Singh; Pali, Puja (Journal of NAST College, 2025)
Sustainable urban mobility hinges on the structural integrity and serviceability of road infrastructure, particularly in developing regions like Nepal, where flexible pavements dominate the arterial network. This study systematically evaluates the failure mechanisms of flexible pavements across six critical urban road segments: Streets 1 to 5 and the Hospital Line of Mahendranagar City, through field inspections guided by ASTM D6433-20 standards. The primary objective was to classify distress types, determine causative factors, and recommend context-appropriate maintenance interventions. The assessment revealed a disproportionately high prevalence of potholes and edge failures, attributed to inadequate drainage, substandard construction practices, and prolonged neglect of routine maintenance. Only Street 1, recently constructed, exhibited no failures. The findings underscore an urgent need for strategic pavement rehabilitation, drainage optimization, and the implementation of a localized pavement management system to ensure long-term performance, user safety, and cost-effective infrastructure sustainability.